El parque de diversiones como laboratorio de física mecánica - Murillo Castañeda, Xiomara del Pilar; Reyes, Jaime Duvan (Revista Científica, 2011)
This paper shows the results of the use of the premises of an amusement park for the appropriation of concepts such as physical, circular motion, work and energy, among others, seen as a lab from the same experience. For this reason we designed and implemented a guidance material, used as a means of learning, which relate the theory, experience and topics of study. The experiment was carried out with a group of students from a mechanical physics from the University Francisco José de Caldas District of Bogota, Colombia, in sessions both in the classroom and in the amusement park and was assessed three times (before during and after the visit to the park). The analysis of results and conclusions show the level of development in the skills, concepts,dimensions of knowledge and strengths of the process, showing an improvement in the significance and construction of the items discussed